Alife in the Clouds: A Short Review of Applications of Artificial Life to Cloud Computing and Back - Merelo-Guervós, Juan-Julián; Castillo, Pedro A.; García-Valdez, Mario (Frontiers in Robotics and AI, 2018)
Cloud computing is currently the prevailing mode of designing, creating and deploying complex applications, and it has implied a paradigm shift in all three areas; even if it taps and extends previous concepts such as service oriented, concurrent and distributed computing, this shift has to be eventually translated to the algorithmic and conceptual aspects of sciences such as artificial life. In this short paper we will review of how the world of cloud computing has intersected the artificial life field, and how it has been used as an inspiration for new models or the design and implementation of new and powerful algorithms; in the other direction, we will also examine how artificial life concepts such as self-organization have been applied to the field of cloud computing.